A construção metafórica do conceito relacionamento: uma perspectiva cognitiva. - Silva, Josilane Márcia Justiniano da (2016)
Linked to a larger project – Metáforas, Gêneros Discursivos e Argumentacão –, this research addresses the analysis of metaphorical linguistic expressions that license conceptual metaphors used to categorize the target domain relationship in three discursive domains: religious, mental health and space virtual. From a cognitive perspective, based on the Conceptual Metaphor Theory (CMT), considered as an Idealized Cognitive Model (ICM) by Lakoff (1987), we make a survey of the main source domains used to map the target domain mentioned. The corpus was constituted of two books that deal with the topic in question (relationship), one from the religious discursive domain and the other from the mental health domain, as well as one hundred and fifty questions gathered from the social networking site Par Perfeito, which we classify as virtual space. The theoretical framework used was the CMT, represented by Lakoff and Johnson (2002 [1980], 2003), Lakoff (1987, 2006 [1993]), Lakoff and Turner (1989), Kövecses (2010 [2002]), among other authors who study this theory; the relationship between metaphor and culture, from the perspective of Lakoff and Johnson (2002 [1980]) and Kövecses (2005); and the interaction between metaphor and ideology, in the perspective of Goatly (2007). Our specific objectives consisted of verifying whether there was a specific conceptual metaphor that characterizes the relationship concept in the investigated corpus, which aspects of the source domains are mapped to the construction of the target domain, and verify if the licensed metaphors are conventional or new. The qualitative analysis of the data showed that the conceptual metaphors used to categorize the relationship concept in general are conventional and are updated by more than one of the investigated discursive domains. Our hypothesis that the linguistic expressions used are influenced by discursive domain was also confirmed from the analysis of the data. In our culture, based on the investigated corpus, we see the use of a source domain group that structures this concept, making clear an ideology of relationship vaunted by religious discourse.